2004
DOI: 10.1136/bjsm.2002.001297
|View full text |Cite
|
Sign up to set email alerts
|

The Victorian Active Script Programme: promising signs for general practitioners, population health, and the promotion of physical activity

Abstract: Background: The Active Script Programme (ASP) aimed to increase the number of general practitioners (GPs) in Victoria, Australia who deliver appropriate, consistent, and effective advice on physical activity to patients. To maximise GP participation, a capacity building strategy within Divisions of General Practice (DGPs) was used. The objectives of the programme were to (a) train and support GPs in advising sedentary patients, and (b) develop tools and resources to assist GPs. Objective: To evaluate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 16 publications
0
61
0
Order By: Relevance
“…Thirteen met the inclusion criteria and were included in the review (figure 1). Five studies originated from the UK (one of them in Scotland),35–39 four from New Zealand,40–43 two from Australia,44 45 and one each from Sweden46 and the Netherlands 47…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen met the inclusion criteria and were included in the review (figure 1). Five studies originated from the UK (one of them in Scotland),35–39 four from New Zealand,40–43 two from Australia,44 45 and one each from Sweden46 and the Netherlands 47…”
Section: Resultsmentioning
confidence: 99%
“…38 Seven studies performed economic modelling using data from a single trial,40 44 46 a meta-analysis of RCTs,37 44 47 a systematic review of randomised and observation studies,35 or a cross-sectional and observational study 45. Four studies reported intermediate outcomes in terms of the cost of making one additional inactive person active;36 39 41 42 five reported final outcomes in terms of incremental cost per DALY44 or QALY40 47 or LYG46 or incremental net health benefit (NHB)37 and four reported both intermediate and cost-utility outcomes 35…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions within general practices had the most favourable cost-effectiveness ratios (€106 per participant to reach at least 3300 kJ expended per week); however, the study was based on modelled rather than actual costs. 34 Gordon et al reviewed the cost-effectiveness of a number of lifestyle interventions for smoking cessation, physical activity, diet, and alcohol reduction. 35 The findings for physical activity interventions generally indicated favourable costeffectiveness: less than €55 860 per QALY, and two studies showed net cost savings.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%